2023
DOI: 10.3390/plants12051007
|View full text |Cite
|
Sign up to set email alerts
|

Surfactin and Spo0A-Dependent Antagonism by Bacillus subtilis Strain UD1022 against Medicago sativa Phytopathogens

Abstract: Plant growth-promoting rhizobacteria (PGPR) such as the root colonizers Bacillus spp. may be ideal alternatives to chemical crop treatments. This work sought to extend the application of the broadly active PGPR UD1022 to Medicago sativa (alfalfa). Alfalfa is susceptible to many phytopathogens resulting in losses of crop yield and nutrient value. UD1022 was cocultured with four alfalfa pathogen strains to test antagonism. We found UD1022 to be directly antagonistic toward Collectotrichum trifolii, Ascochyta med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that the Bacillus subtilis strain UD1022 exerts beneficial effects on plant growth and offers protection against plant pathogens [ 13 , 23 , 45 , 46 , 53 ]. Most experiments involving plant growth-promoting rhizobacteria (PGPR) are conducted using artificial soil or under controlled laboratory conditions [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the Bacillus subtilis strain UD1022 exerts beneficial effects on plant growth and offers protection against plant pathogens [ 13 , 23 , 45 , 46 , 53 ]. Most experiments involving plant growth-promoting rhizobacteria (PGPR) are conducted using artificial soil or under controlled laboratory conditions [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The B. subtilis strain UD1022 eps−TasA− , which is defective for the EPS and TasA genes, was obtained in a previous study [ 53 ]. Wild-type B. subtilis was cultivated on Luria broth (LB) agar plates, and its respective mutant was cultivated on LB supplemented with 5 µg mL −1 tetracycline and 1 µg mL −1 erythromycin.…”
Section: Methodsmentioning
confidence: 99%
“…Biological control methods are also available for the control of ASBS. Leaf lesion areas pre-colonized by P. medicaginis failed to develop, when those lesions were sprayed with conidial suspensions of Cladosporium cladosporioides or Penicillium citrinum [88], with AM fungi Funneliformis mosseae or Rhizophagus intraradices, with the rhizobium Sinorhizobium medicae [89,90], and with Bacillus licheniformis [91] or with B. subtilis [92]. Also, Streptomyces inoculated onto the seed at the time of planting or onto leaves also showed potential to reduce leaf spot caused by P. medicaginis incidence and index under greenhouse conditions [88].…”
Section: Biological Controlmentioning
confidence: 99%
“…B. subtilis strain L194 also alleviates disease symptoms by reducing germination of P. medicaginis conidia [95]. B. subtilis strain UD1022 is directly antagonistic not only towards P. medicaginis, but also towards Collectotrichum trifolii and Phytophthora medicaginis [92]. B. subtilis can also control alfalfa root rot disease.…”
Section: Biological Controlmentioning
confidence: 99%
See 1 more Smart Citation